Synapto-pHluorins: genetically encoded reporters of synaptic transmission. - Miesenböck, G (2012)
pHluorins are pH-sensitive mutants of green fluorescent protein (GFP). Attached to proteins with defined cellular locations or itineraries, pHluorins report subcellular pH as well as protein transport between compartments of differing pH. Key applications in neurobiology include the optical detection of neurotransmitter release with synapto-pHluorins and their derivatives, as well as measurements of neurotransmitter receptor trafficking. This article describes the properties and uses of synapto-pHluorins, as well as their advantages and limitations.